PROFESIONALISME AUDITOR INTERNAL DAN PERANNYA DALAM PENGUNGKAPAN TEMUAN AUDIT - SISWATI, YENI (: 2303-1719)
Control is an essential element in the management of a company and can help an entity achieve maximum profits, preventing the loss of its resources, and help ensure reliable financial reporting. Control in a company held by the company management, so that the internal auditor's role is crucial, therefore, the internal auditor duties required to be professional. A professional internal auditor must have a dedication to the profession, social responsibility, the demands of autonomy, believing in their own setting, and have a gathering profession. With its rofessionalism, will create an internal auditor to work with independent and better, so that in case of irregularities in the company, this may be unknown, and disclosed in the audit findings. These findings will be useful to help prevent the occurrence of repeated irregularities in the future.